Conditionality in Evolving Monetary Policy Regimes. (Policy Papers; Policy Paper ;, 2014)
With single-digit inflation and substantial financial deepening, developing countries are adopting more flexible and forward-looking monetary policy frameworks and ascribing a greater role to policy interest rates and inflation objectives. While some countries have adopted formal inflation targeting regimes, others have developed frameworks with greater target flexibility to accommodate changing money demand, use of policy rates to signal the monetary policy stance, and implicit inflation targets.